Apakah Ukuran Perusahaan dan Profitabilitas Berpengaruh terhadap Penghindaran Pajak pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2022-2024? - Irma Rezki Saputri; Mustika Mutiara Dewi Laras; Tania Wulandari; Reventina Natalia; Rimi Gusliana Mais (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2026)
This study aims to analyze the effect of company size and profitability on tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The research uses secondary data obtained from published financial statements, with a sample of 333 companies selected through a purposive sampling technique. Panel data regression is employed as the main analytical method to examine the relationship between the independent variables and tax avoidance practices. The results of the analysis indicate that profitability has a positive and significant effect on tax avoidance, suggesting that more profitable companies tend to engage more actively in tax planning strategies to reduce tax burdens. In contrast, company size is found to have no significant effect on tax avoidance, indicating that large and small manufacturing firms exhibit similar tax behavior. Overall, this study provides empirical evidence regarding the determinants of corporate tax avoidance and contributes to the literature by offering insights for policymakers, regulators, and stakeholders in understanding tax avoidance behavior in the manufacturing sector.